Flood Routing Model Using Genetic Expression Programing - Onen Fevzi; Ok Oral Safak (European Scientific Journal, ESJ, 2017)
A change depending on the time of the flood wave moving in a stream using flood routing approach is examined. Flood routing of flood discharge along the river with their account and calculating the changes in the water level of flood protection structure size is determined to safety. The aim of this study, Sutculer flood event will be modeled by Genetic Expression Programing (GEP) method. The GEP method makes use of few hydrologic parameters such as inflow, outflow, and time. Simulation results indicate that the proposed a predictive model is an appropriate for the flood routing. Case study is presented to demonstrate that the GEP model is an alternative in implementation of the Muskingum model.